Platinum-osmium heterometallic clusters containing N-heterocyclic carbene ligands and an electron-deficient tetraosmium by-product - Liu, Yu (2020)
The room temperature reaction of [Os 3 (CO) 12 ] (1) with three molar equivalents of [PtCl(allyl)(NHC)] (2) in the presence of KOtBu afforded the heterometallic clusters [PtOs 3 (CO) 12 (NHC)] (3), [Pt 2 Os 3 (CO) 12 (NHC) 2 ] (4), and [Pt 3 Os 3 (CO) 12 (NHC) 3 ] (5), together with a trace amount of the tetraosmium cluster [Os 4 (CO) 10 (µ-H) 2 (NHC)] (6). The reaction pathway is thus similar to that for Pd analogues, with the exception of cluster 6. Unlike their Pd analogues, however, these clusters do not appear to readily interconvert. With a valence electron count of 58, clusters 6 are deficient by four electrons.